Creative Problem-Solving Learning Model to Improve Student Activeness and Learning Outcomes in Entrepreneurship Creative Product Subject - Fachrul Rahman (Jurnal Guru Komputer, 2021)
To overcome this problem, a study was conducted using the Creative Problem Solving learning model to increase student activeness and understanding in learning. This study aims to determine whether or not there is an increase in student activity and learning outcomes.This type of research is Classroom Action Research which is conducted in two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The success indicators determined were the average score of the student's activeness level reaching ≥75% and the percentage of classical completeness of students in the class reaching ≥75%. The results showed that there was an increase in student activeness and learning outcomes, this is evident from the percentage of classical student completeness from the pre-cycle which was only 22% increased to 63% in cycle I and again increased in cycle II reached 88%, while the percentage of observation results The activeness of students in the first cycle reached 67% then increased in the second cycle to 83%. Based on the results of research and discussion, it can be concluded that there is an increase in student activeness and learning outcomes after the application of the Creative Problem Solving (CPS) learning model in the subject of computer assembly, basic competence in understanding the disassembly procedures of computers and presenting the results of assembling computers.